AI Dan Pembelajaran Mendalam (Deep Learning): Meningkatkan Kualitas Pendidikan Di Era Digital - Rissi, Andrie Riomalen Yordan; Sinaga, Dameria (Cetta: Jurnal Ilmu Pendidikan, 2025)
The Indonesian government continues to update the Merdeka Curriculum to create an education system that is responsive and relevant to the demands of the times, including by adopting a deep learning approach supported by artificial intelligence (AI). However, this implementation faces challenges such as limited infrastructure, teacher competency, and unequal access to technology in remote areas. This study aims to explore how artificial intelligence and online learning can improve the quality of education in the digital age. It employs a literature review approach to gather information from various relevant, comprehensive, and up-to-date sources, and analyzes the data using descriptive methods. The findings of this study reveal that artificial intelligence can personalize learning experiences based on each student's needs, such as adapting content and teaching techniques, identifying difficult areas, and providing relevant supplementary materials. The study also highlights various challenges and obstacles in implementing AI, including technological infrastructure readiness, teachers' understanding, as well as cultural, religious, ethical, and data privacy concerns, along with its impact on teachers and the curriculum. In conclusion, artificial intelligence (AI) and deep learning can enhance the effectiveness of learning in the digital era through adaptive personalization and interactivity. However, their success depends on proper curriculum integration, teacher training, data protection, and equitable infrastructure development to address technological, ethical, and access-related challenges comprehensively. With proper integration, AI has the potential to create a more efficient, effective, and individualized learning environment.